الاستثمار الأمثل للموارد المائية في القطاع الزراعي دراسة تطبيقية في المنطقة السّاحلية خلال الفترة (2002-2012) - طيوب, محمود; الحداد, خلدون (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى تقدير كميات المياه المخصصة لإرواء المساحات الزراعية في المنطقة الساحلية خلال الفترة 2002-2012، في حال تمّ استخدام الري الحديث (الري بالتنقيط والري بالرذاذ) بدلاً من الري السطحي التقليدي، وفق المقنن المائي لكل طريقة ومعدل كفاءتها, بالإضافة إلى تقدير الفاقد في شبكات الري الحكومية المخصصة للزراعة ، ووضع آليات التسعير المناسبة. اعتمد البحث على المنهجين التاريخي والوصفي, وكان من أهم النتائج: 1- أظهرت النتائج أنه لو تمّ استخدام الري بالتنقيط بدل الري السطحي في إرواء المساحات الزراعية المعتمدة على الري السطحي لأسهم ذلك في توفير ما مقداره (40%) من كميات المياه المستخدمة في الري السطحي, وبمتوسط بلغ (174973785) متراً مكعباً خلال الفترة 2002-2012. 2- أظهرت النتائج أنه لو تمّ استخدام الري بالرذاذ بدل الري السطحي في إرواء المساحات الزراعية المعتمدة على الري السطحي لأسهم ذلك في توفيره ما مقداره (28%) من كميات المياه المستخدمة في الري السطحي, وبمتوسط بلغ (122481649) متراً مكعباً خلال الفترة المدروسة. 3- يختلف التسعير الاقتصادي للطلب الزراعي على المياه عن التسعير الحالي, حيث تبين أنّ هناك عجزاً في استرداد تكاليف التشغيل والصيانة لأراضي المزارعين المستفيدين من مياه شبكات الري الحكومية، والبالغة (21500) للهكتار الواحد, بالمقارنة مع ما يتم تحصيله (3500) ل. س للهكتار الواحد. The research aims to estimate allocated to quench agricultural areas in the coastal region, the amount of water during the period 2002-2012 in case of the use of modern irrigation (drip and sprinkler irrigation) instead of the traditional surface irrigation according to water legalized each method and the rate of efficiency, as well as to estimate the losses in irrigation networks allocated to agriculture and the development of appropriate pricing mechanisms of government. Find the historical and descriptive approaches adopted, and it was the most important results: 1- The results showed that if the use of drip irrigation surface irrigation in the quench-based surface irrigation acreage allowance contributed to supply up to 40% of the water used in surface irrigation amounts, and an average (174 973 785) cubic meters during the period 2002- 2012. 2- The results showed that if the use of sprinkler irrigation surface irrigation instead of the quench-based surface irrigation acreage for contributed to the supplied amount to 28% of the water used in surface irrigation amounts, and an average (122 481 649) cubic meters during the period studied. 3- economic pricing of agricultural water demand for current pricing varies, it was found that there is a deficit in the recovery of operating and maintenance costs of the territory of farmer beneficiaries of the water public irrigation networks and adult (21,500) per hectare, compared with what is being collected (3500) for. Q per hectare.